2018
DOI: 10.3390/su10114139
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Factors Affecting Consumers’ Willingness to Accept Clothing Rentals

Abstract: Fashionable clothes resource suppliers are directly linked with resource consumers through the Internet, thus replacing the traditional model. With fashionable clothes as the products for renting, this study helps relevant enterprises understand the factors influencing consumers' adoption of renting and their attitude and behavioral intention towards clothes renting. Taking the theory of planned behavior as the theoretical foundation, this study thus adopts the technology acceptance model (TAM), the innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
(118 reference statements)
2
24
0
Order By: Relevance
“…This finding is in line with earlier research Vehmas and Raudaskoski [52] that showed consumers are more interested in finding their own personal fashion needs and then focus on the ethical issues. It was consistent with Maloney and Lee [26] and Tu and Hu [36] that showed the most significant factor on purchase intention is an attitude which was followed by the perceived behavioural control and then subjective norms on the construct intention. Moreover, according to qualitative results, touching the clothes is the most important factor, particularly for women, which agrees well with the findings in extant studies [3,18,53].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is in line with earlier research Vehmas and Raudaskoski [52] that showed consumers are more interested in finding their own personal fashion needs and then focus on the ethical issues. It was consistent with Maloney and Lee [26] and Tu and Hu [36] that showed the most significant factor on purchase intention is an attitude which was followed by the perceived behavioural control and then subjective norms on the construct intention. Moreover, according to qualitative results, touching the clothes is the most important factor, particularly for women, which agrees well with the findings in extant studies [3,18,53].…”
Section: Discussionsupporting
confidence: 87%
“…Wiriyapinit [35] discovered that the family norm instructed by parents can influence purchase intentions of products in Thailand. The literature on this aspect also indicates that subjective norm as a perceived social demand for executing a particular behaviour has a positive influence on behavioural purchase intention of Eco-fashion products [17,36]. In line with the discussion in the literature on this subject, we hypothesize that: H2.…”
Section: B Subjective Norms Toward Eco-fashion Clothes and Purchase supporting
confidence: 56%
“…Rooted in social psychology, the Theory of Reasoned Action (TRA) is used extensively to capture consumers' decision-making processes in a variety of areas [14]. Previous literature has found that both consumers' attitudes toward online shopping and their online fashion renting behavior has a positive influence on their behavioral intentions [15,16]. Across different disciplines and industries, studies on collaborative consumption have investigated two critical factors, relative advantage and environmental considerations, which often lead to participation in collaborative consumption [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al reported "A Study on the Factors Affecting Consumers' Willingness to Accept Clothing Rentals" [25]. This study adopts the technology acceptance model (TAM), the innovation diffusion theory (IDT), the structural equation model (SEM), and the collected information to develop a research methodology that is both theoretical and practical.…”
Section: Tu Et Al Reported "Key Factors Of Sustainability For Smartpmentioning
confidence: 99%
“…The Second Eurasian Conference on Educational Innovation 2019 (ECEI 2019) was held in Singapore, [25][26][27] January 2019, and provided a communication platform for researchers on the topic of educational innovations. This conference aims to enable interdisciplinary collaboration between educators and experts from other areas in the academic and industrial fields, as well as international networking.…”
Section: Introductionmentioning
confidence: 99%